Enhancing mercury removal across air pollution control devices for coal-fired power plants by desulfurization wastewater evaporation. Issue 2 (15th January 2019) - Bin, Hu; Yang, Yi; Cai, Liang; Yang, Linjun; Roszak, Szczepan
ABSTRACT: Desulfurization wastewater evaporation technology is used to enhance the removal of gaseous mercury (Hg) in conventional air pollution control devices (APCDs) for coal-fired power plants. Studies have affirmed that gaseous Hg is oxidized and removed by selective catalytic reduction (SCR), an electrostatic precipitator (ESP) and wet ﬂue gas desulfurization (WFGD) in a coal-fired thermal experiment platform with WFGD wastewater evaporation. Effects of desulfurization wastewater evaporation position, evaporation temperature and chlorine ion concentration on Hg oxidation were studied as well. The Hg 0 oxidation efﬁciency was increased ranging from 30% to 60%, and the gaseous Hg removal efficiency was 62.16% in APCDs when wastewater evaporated before SCR. However, the Hg 0 oxidation efﬁciency was 18.99% and the gaseous Hg removal efficiency was 40.19% in APCDs when wastewater evaporated before ESP. The results show that WFGD wastewater evaporation before SCR is beneficial to improve the efficiency of Hg oxidized and removed in APCDs. Because Hg 2+ can be easily removed in ACPDs and WFGD wastewater in power plants is enriched with chlorine ions, this method realizes WFGD wastewater zero discharge and simultaneously enhances Hg removal in APCDs.